Recent perspectives on trade and inequality - Harrison, Ann; McLaren, John; McMillan, Margaret S. (Annual Reviews, 2011)
The 1990s dealt a blow to traditional Heckscher-Ohlin analysis of the relationship between trade and income inequality, as it became clear that rising inequality in low-income countries and other features of the data were inconsistent with that model. As a result, economists moved away from trade as a plausible explanation for rising income inequality. In recent years, however, a number of new mechanisms have been explored through which trade can affect (and usually increase) income inequality. These include within-industry effects due to heterogeneous firms, the effects of offshoring of tasks, effects on incomplete contracting, and the effects of labor-market frictions. A number of these mechanisms have received substantial empirical support.